Women's Legislative Leadership and Substantive Representation in the Ratification of the TPKS Law - Rafifrian Evandio; Cecep Hidayat (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Increased women's representation in parliament is often assumed to be directly proportional to the development of gender-responsive policies. This article challenges this assumption by analyzing women's legislative leadership in the enactment of the Sexual Violence Crime Law (TPKS Law) through the perspective of substantive representation. Unlike previous studies that have focused on descriptive representation or the advocacy role of civil society, this article offers a novel approach by positioning women's legislative leadership as institutional actors operating through formal authority and legislative mechanisms. This research employs a qualitative approach with policy analysis methods, based on a documentary study of minutes of House of Representatives meetings, institutional releases, and media coverage of the TPKS Law legislative process. The analysis is conducted by linking empirical findings to Hanna Pitkin's indicators of substantive representation, including agenda management, political decision-making, policy outcomes, and leadership consistency. The research findings indicate that the enactment of the TPKS Law resulted from political actions and strategic decisions by House leaders, who were able to maintain the continuity of the legislation amidst ideological resistance. This article asserts that women's substantive representation is not inherent to gender identity but is mediated by institutional structures and formal authority within the legislative process.